2023
DOI: 10.1186/s12887-023-03935-0
|View full text |Cite
|
Sign up to set email alerts
|

Known risk factors of the developmental dysplasia of the hip predicting more severe clinical presentation and failure of Pavlik harness treatment

Abstract: Purpose Developmental dysplasia of the hip (DDH) varies from mild instability of the hip to subluxation or total dislocation of the joint. Well-known risk factors of DDH include pre-natal breech position, female sex, positive family history, hip side, primiparity and the mode of delivery. Aim of the present study was to further evaluate known risk-factors of DDH, find associations with more severe dysplasia (characterized with Ortolani positivity) and find risk factors of failure of the Pavlik … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…Same results were found with children with family history compared to children without family history. These ndings support our earlier ndings, where we found girl sex and family history to be risk for late recovery 24 and failure of the abduction treatment 21 . Our results in this study further explain the mechanism through which these risk factors effect on the recovery of DDH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Same results were found with children with family history compared to children without family history. These ndings support our earlier ndings, where we found girl sex and family history to be risk for late recovery 24 and failure of the abduction treatment 21 . Our results in this study further explain the mechanism through which these risk factors effect on the recovery of DDH.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that dislocation and irreducibility increase the risk of failure of the abduction treatment 9,12,18,19 , and some studies have also associated bilaterality with treatment failure 7,19,20 . In our earlier study we found, that girl sex and family history might predispose to treatment failure 21 .…”
Section: Introductionmentioning
confidence: 86%
“…Our results indicate that family history might predispose to more severe forms of DDH (characterized as low alpha angles and major hip instability at one month´s age). To our knowledge, there are no previous studies investigating the risk factors relation to the severity of DDH, despite our own previous study, where we found that girl sex and positive family history increase the risk of Ortolan positive DDH, and positive family history might increase the risk of casting and/or operation 21 . In our data it seemed, that positive family history was overrepresented among the children who failed the initial treatment (45% of the children who failed vs 22.3% of all children).…”
Section: Discussioncontrasting
confidence: 66%
“…In our earlier study we have found, that girl sex and positive family history might increase the risk for late recovery 23 . Moreover, they seem to be risk factors for Ortolani positivity and might predispose to abduction treatment failure 21 . Several studies have found lower success rates of abduction treatment in more severe forms of DDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation